CLINICAL FEATURES AND OUTCOMES OF PATIENTS WITH METASTATIC BREAST CANCER - RASHID , AA; TOOR , MT; MUNIR , AB; ABRO , NA; SHAFIQ , B (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Oncology, Hameed Latif Hospital, JPMC & GINUM, from January 2020 to January 2023 to assess the shift in the prognosis of MBC over time in the real-life clinical setting. Patients were divided into groups based on disease diagnosis (Group I: January 2020-January 2021 and Group II: January 2022-January 2023) and disease presentation (de novo vs. recurrent), and the correlation between prognostic factors and survival was assessed. A total of 781 patients were included in the study, 240 in Group I and 541 in Group II. There were 484 (61.9%) HR+, 210 (26.8%) HER2+, and 86 (11.01%) TN cases. 412 (53%) had recurrent disease, with a gradual increase in frequency (P <0.001). Incidence of HR+ disease (56%) was significantly higher than HER2+(20%) and TN subtypes (12%)(P<0.001). 375 (48%) had dnMBC, consisting of 52% with HR+ disease, 29% withHER2+ and 5.8% having TNMBC. Despite a gradual decrease in frequency, de novo disease was most common in the HER2+ subtype (62% in Group I vs. 49% in Group II, P = 0.007). A higher number of subjects with HR+ disease had chemotherapy in Group I compared to Group II (P=0.01), while endocrine therapy (ET) was more common in Group II (n = 238, 44%) compared to Group I (n = 118; 38.4%) (P=0.14). There were significant variations among pathological subtypes; HR+ was 18.0 months, HER2+ was 17.0 months, and TNBC was 10 months ( P< 0.001). The median OS among all patients after a follow-up of 36 months was 50.0 (47.0-54.0) months. TN group had the worst OS of 27 months (P<0.001). The impact of modern treatment approaches in Group I vs. Group II (52 vs. 52 months) was insignificant. Advancement in the treatment is associated with improved prognosis of MBC, particularly for luminal B-HER2+. TNBC has the worst prognosis and is the most challenging to treat. The findings of this study will provide insight into disease patterns and survival, which can be valuable for improving outcomes through the use of novel treatment.